Technique for Satellite Monitoring of Illegal Amber Mining Territories Based on Integrated Landsat and Sentinel Data Processing - Shevchuk, Ruslan M. (Journals of Georgian Geophysical Society, 2018)
This paper is devoted to the use of multispectral satellite imagery for monitoring and effective control of illegal amber mining. The main problems that prevent implementation of these tasks are the existence of a large number of sand dumps in mining places that are different in origin and difficult to distinguish its origin; “amber rush” territorial distribution covers very large areas (near 14,000 sq km); part of mining sites are guarded by criminal and, as consequence, inaccessible for ground truth research. To solve these problems new monitoring technique is proposed. The technique based on fusion of free Landsat and Sentinel data and takes into account spectral and thermal differences between disturbed by illegal amber mining lands and surrounded landscapes. The results of technique application over Olevsk district of Zhytomyr region are demonstrated.